2020
DOI: 10.47405/mjssh.v5i12.563
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning Adoption: A perspective from a Form Six Students in Sabah, Malaysia

Abstract: Despite the availability of studies on mobile learning adoption, its theoretical foundations have not yet matured. However, studies on mobile learning adoption in the context of form six student in Malaysia is still very limited. Against this concern, a study was conducted with the aim of investigating factors that could influence the adoption of mobile learning. Based on The Unified Theory of Acceptance and Use of Technology (UTAUT) and two other variables which are Perceived Playfulness and Self-Directed Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The findings echo those of [111], who found that primary school is the least studied educational level in MALL research. The scarcity of studies examining MALL integration in the context of primary school students in Malaysia is because mobile learning has not been incorporated formally within the framework of primary school instruction due to the policy prohibiting primary school students from using mobile devices in school [80], [114], [115].…”
Section: Educational Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings echo those of [111], who found that primary school is the least studied educational level in MALL research. The scarcity of studies examining MALL integration in the context of primary school students in Malaysia is because mobile learning has not been incorporated formally within the framework of primary school instruction due to the policy prohibiting primary school students from using mobile devices in school [80], [114], [115].…”
Section: Educational Levelmentioning
confidence: 99%
“…This scenario could be because the school authorities involved in the studies permitted upper-form students to bring mobile phones to school, allowing teachers to plan formal and informal MALL activities to supplement English instruction without relying on non-formal activities that were more difficult to plan and execute. Nevertheless, due to the current policy prohibiting the use of mobile phones on school grounds [80], [114], [115], [119], [120], MALL integration at the primary school level was conducted exclusively outside of the classroom setting, with both intentional and unintentional learning activities aimed at enhancing students' English language acquisition.…”
Section: Learning Contextmentioning
confidence: 99%
“…However, the learning process is a two-way interactive process with the essential elements being the instructor and the student; thus, this study incorporates the variables of instructor readiness and student readiness into the research framework. Mobile learning places the student in the center of the entire learning activity, and the student-centered learning process allows students to choose when and how often they learn, making student self-directed learning a significant factor influencing mobile learning adoption (Kankok et al, 2020).…”
Section: Introductionmentioning
confidence: 99%